Conservation status of Lagothrix flavicauda and other primates in montane forest of San Martín and Huánuco, Peru - Aquino, Rolando (2017)
Lagothrix flavicauda is endemic and lives sympatrically with other primates in the montane forests of Amazonas, San Martín, La Libertad and Huánuco. Detailed information on its density and conservation status, as well as sites with healthy populations is lacking, except for Amazonas where most of the studies were carried out. In order to obtain information on the mentioned aspects, transect censuses were conducted between November and December of 2015, February to May of 2016, and between June and July of 2016 in six survey sites located in the regions of San Martín and Huánuco. As a result of the census, 49 groups belonging to 7 species were sighted, being L. flavicauda the most observed with 14 groups. The largest groups were observed in L. flavicauda (average 13.5±2.2 individuals) and Cebus yuracus (average 12.5±3.6 individuals) and the smallest in Alouatta seniculus (average 3.0± 2.4 individuals), both in Huánuco. The relative abundance was the highest for L. flavicauda in San Martín (2.4 individuals /10 km) and the lowest for A. seniculus in Huánuco (0.2 individuals/ 10 km). Our observation of L. flavicauda on the eastern side of the Huallaga River extends its distribution in Huánuco to the Pozuzo River, but on the western side we can consider it locally extinct in much of its distributional range. At our survey sites, deforestation and hunting are the main threats to primates and other components of wildlife.